Pengaruh Identitas Visual terhadap Loyalitas Konsumen pada Produk Lokal - Novia Indah Lestari; Putri Wening Ratrinia; Naufal Aulia Fiermeiza; Akhmad Taufik (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
Visual identity is a strategic concern for local SMEs because consumers increasingly evaluate products through visible brand cues across digital and physical channels. This study analyzes the influence of logo, color, typography, and packaging design on consumer loyalty toward local SME products in Serang City. The study used a quantitative survey design with 25 consumers selected through purposive sampling. The inclusion criteria required respondents to live in Serang City, be at least 17 years old, and have purchased local SME products at least twice in the previous three months. Data were collected using a five point Likert scale questionnaire and analyzed through multiple linear regression with SPSS 26. The results show that logo, color, typography, and packaging design have positive and significant partial effects on consumer loyalty. The simultaneous test also confirms that visual identity significantly explains consumer loyalty, with an R squared value of 0.589. Color has the strongest effect, followed by logo, packaging design, and typography. These findings imply that consistent visual identity can help local SMEs strengthen product recognition, reduce perceived risk, and build long term loyalty. The study recommends that SME actors develop simple visual guidelines for logos, colors, typography, packaging, and digital content.